Factors associated with voice-related quality of life among patients with temporomandibular disorders - Emshoff, Rüdiger; Astl, Magdalena; Giotakis, Aris Ioannis; Hupp, Linus Christian; Kolk, Andreas (Journal of Applied Oral Science, 2024)
Research would be important for obtaining a better understanding of voice complaints among patients with temporomandibular disorders (TMD). Objective: The identification of predictors of voice disorders associated with TMD pain was made according to Diagnostic Criteria for TMD (DC/TMD) Axis I. Methodology: Functional limitations were measured using the Jaw Functional Limitation Scales for mastication (JFLS-M), jaw mobility (JFLS-JM), and verbal and emotional expression (JFLS-VEE). Patients also completed the Hospital Anxiety and Depression Scale (HADS). The primary outcome was social-emotional and physical functioning as indicated by scores on the Voice-Related Quality of Life (V-RQOL) questionnaire. Multiple linear regression was used to model the relationship between the domains on the V-RQOL questionnaire and scores on the HADS and JFLS after adjusting for age, gender, DC/TMD diagnosis, pain intensity, and time since pain onset. Results: The HADS-D (B=-1.15; 95% CI, -1.718 to -0.587; p<.001) and JFLS-VEE (B=-0.22; 95% CI, -0.40 to -0.06; p=.008) were significant predictors of scores on the V-RQOL questionnaire. Conclusion: Higher scores on depression measures and limitations in verbal and emotional expression could exacerbate voice problems among TMD pain patients. Future research should promote multidisciplinary treatments for TMD pain-related voice disorders.